Data outsourcing authentication model based on authenticated data structures for cloud computing - XU Jian1; ZHOU Fu-cai1; CHEN Xu1; ZHU Zhi-liang2 (Tongxin xuebao, 2011)
The outsourcing authentication model based on authenticated data structures was proposed.The formal defini-tion,data query authentication protocol and data updating authentication protocol of the model was presented.The crucial problems when the authenticated data structures are being used were analyzed.With designing the new extended coher-ence proof generation algorithm and the new extended verifying algorithm,authenticated data structures in the model very well was used.Finally the model with others through the performance analysis including the security and efficiency,the results of which show that:the model is more efficient than others as well as the consistency and correctness require-ments are also guaranteed.